2005
DOI: 10.1007/s10350-004-0948-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates After Abdominal Surgery for Complete Rectal Prolapse: A Multicenter Pooled Analysis of 643 Individual Patient Data

Abstract: Although this study is likely underpowered, the impact of mobilization-only on recurrence rates was similar to that of other surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 11 publications
6
48
0
3
Order By: Relevance
“…9 In this work, the demographic data of both laparoscopic and open groups showed that most of our patients were female with the mean age 48 and 52 years respectively, this was consistent with other similar studies. 8,[15][16][17][18] During the laparoscopic procedure, we used four port sites to perform the laparoscopic posterior mesh repair for FTRP, this is in agreement with other many studies. [8][9][10] Also, in this study, the operative time in laparoscopic group is more than open group, but without significant statistical difference (P value 0.45).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…9 In this work, the demographic data of both laparoscopic and open groups showed that most of our patients were female with the mean age 48 and 52 years respectively, this was consistent with other similar studies. 8,[15][16][17][18] During the laparoscopic procedure, we used four port sites to perform the laparoscopic posterior mesh repair for FTRP, this is in agreement with other many studies. [8][9][10] Also, in this study, the operative time in laparoscopic group is more than open group, but without significant statistical difference (P value 0.45).…”
supporting
confidence: 64%
“…These recorded results were close to the incidence of other similar studies that was ranged from 0-13% after abdominal posterior mesh rectopexy. 1,17,26 Patients with FTRP have markedly impaired rectal adaptation to distention, which may contribute to anal incontinence, and consequently more than half of the patients with rectal prolapse have coexisting incontinence. 22 Improvement of fecal incontinence is 3-40% after abdominal posterior mesh rectopexy.…”
mentioning
confidence: 99%
“…Authors were selected based on their previous contributions to the current literature and/or participation in the Rectal Prolapse Recurrence Study Group. 7 There was consistent contact between the study coordinator and the participating centers.…”
Section: Participating Centers and Surgeonsmentioning
confidence: 99%
“…4 -6 A pooled analysis of 643 individual patient data collected from 15 institutions concluded that rectal mobilization without rectopexy is as effective as rectopexy with respect to recurrence rates. 7 However, despite the large number of patients, this was a retrospective data collection. Therefore, adequately powered and rigorous RCTs are needed.…”
mentioning
confidence: 99%
“…Permanent anatomical correction of the structural defect and optimal functional result are the principal purposes of the surgical treatment of rectal prolapse [1,2]. Although the rate of recurrence rises to 50% of patients, on the basis of the literature, there are limited data regarding the possible causal factors of relapse and the treatment options available [3][4][5].…”
Section: Introductionmentioning
confidence: 99%